Evaluation of the incremental effect of fasting length on pH, select cecal microbial groups, cecal volatile fatty acid concentrations, and secretory IgA excretion in roosters - B.W. Parsons; M.R. Bedford; C.L. Wyatt (Poultry Science)
Two experiments were conducted to evaluate the effect of incremental fasting time on the gastrointestinal tract in chickens. Adult White Leghorn roosters with intact ceca were provided a nutrient-adequate corn-soybean meal diet ad libitum for 3 weeks. Prior to initiation of the experimental phase, ad libitum feed intake was recorded for 8 h and immediately after the fasting period commenced. In Experiment 1, roosters were fasted for either 0, 3, 6, 9, 12, 16, or 24 h. At each time point birds were euthanized and pH in the crop, gizzard, and ceca were recorded and cecal contents were collected to measure volatile fatty acids (VFA) and select cecal microbial groups. In Experiment 2, roosters were fasted for 0, 3, 6, 9, 12, 16, and 24 h and excreta were collected to determine secretory IgA (sIgA) excretion. In contrast to Experiment 1, roosters in Experiment 2 were not euthanized and thus sIgA excretion was measured within individual roosters across each time point. Experiments 1 and 2 contained 5 and 8 replicates per treatment, respectively. In Experiment 1, there was a linear increase (P < 0.05) in cecal pH as fasting length increased. Cecal VFA content was reduced (P < 0.05) by 9 to 12 h of fasting and branch-chain FA to VFA ratio increased (P < 0.05) by 6 h of fasting. There were few effects (P > 0.05) of fasting on the microbial groups in cecal contents and mucosa; however, Escherichia coli content was greater (P < 0.05) at 24 h of fasting compared with other time points. In Experiment 2, total sIgA excreted was greater (P < 0.05) at 24 h of fasting, being 1106 µg/h at 24 h compared with a mean of 419 µg/h for all other time points. In conclusion, fasting reduced cecal VFA concentrations and increased cecal pH, Escherichia coli, branched-chain FA to VFA ratio, and sIgA excretion, suggesting that fasting elicited negative effects on the gastrointestinal tract.